Emergency department use for acute rhinosinusitis: Insurance dependent for children and adults. (21st July 2017) - Bergmark, Regan W.; Ishman, Stacey L.; Phillips, Katie M.; Cunningham, Michael J.; Sedaghat, Ahmad R.
Abstract : Objectives/Hypothesis: Patients with Medicaid or self‐pay insurance status are more likely to present to the emergency department (ED) for uncomplicated acute rhinosinusitis (ARS). Our aim was to determine if this pattern holds true for both pediatric and adult visits. Study Design: Cross‐sectional study using the 2005 to 2012 National Hospital Ambulatory Medical Care Surveys and National Ambulatory Medical Care Surveys. Methods: We included all visits with International Classification of Diseases, Ninth Revision codes for ARS and without codes for ARS complications. We tested for associations between insurance type and presentation to an ED versus a primary care physician (PCP), stratifying children versus adults. We used univariate and multivariable logistic regression modeling, controlling for clinical and demographic characteristics for analysis. Results: There were 51, 579, 977 uncomplicated ARS visits to PCPs (48, 213, 335 visits) and EDs (3, 366, 642 visits). Medicaid and uninsured patients were under‐represented for ARS visits. Medicaid insurance was significantly associated with ED presentation for ARS for both children (adjusted odds ratio [OR] = 7.0, P < 0.001) and adults (adjusted OR = 6.8, P < 0.001). Children with ARS and self‐pay insurance status were much more likely to present to the ED (adjusted OR = 48.8, P < 0.001) than adults (adjusted OR = 5.2, P < 0.001); this difference between children and adults with self‐pay insurance was significant ( P = 0.001). Conclusion: With respect to absolute numbers of visits, patients with Medicaid or no insurance use less care overall for uncomplicated ARS than do privately insured patients. Medicaid is associated with ED presentation for ARS for pediatric and adult visits. Self‐pay insurance status is strongly associated with ED presentation for adult and pediatric visits, and is significantly more common for children. These results suggest limitations in primary care access for uncomplicated ARS based on insurance status, particularly for uninsured pediatric patients. Level of Evidence: 4. Laryngoscope, 128:299–303, 2018